2014
DOI: 10.1088/0957-4484/25/27/275501
|View full text |Cite
|
Sign up to set email alerts
|

Slowing single-stranded DNA translocation through a solid-state nanopore by decreasing the nanopore diameter

Abstract: To slow the translocation of single-stranded DNA (ssDNA) through a solid-state nanopore, a nanopore was narrowed, and the effect of the narrowing on the DNA translocation speed was investigated. In order to accurately measure the speed, long (5.3 kb) ssDNA (namely, ss-poly(dA)) with uniform length (±0.4 kb) was synthesized. The diameters of nanopores fabricated by a transmission electron microscope were controlled by atomic-layer deposition. Reducing the nanopore diameter from 4.5 to 2.3 nm slowed down the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 28 publications
5
49
0
Order By: Relevance
“…Details of the preparation process used for the 5.3-kb ss-poly(dA) are described in ref. 24 , which reported that the variation in the length of ss-poly(dA) was approximately 5.3-kb ± 0.4-kb. In this paper, we hereafter refer to 5.3-kb ± 0.4-kb ss-poly(dA) as poly(dA) 5.3k .…”
Section: Resultsmentioning
confidence: 99%
“…Details of the preparation process used for the 5.3-kb ss-poly(dA) are described in ref. 24 , which reported that the variation in the length of ss-poly(dA) was approximately 5.3-kb ± 0.4-kb. In this paper, we hereafter refer to 5.3-kb ± 0.4-kb ss-poly(dA) as poly(dA) 5.3k .…”
Section: Resultsmentioning
confidence: 99%
“…In order to pass single-stranded DNA, the diameter of the pore must be at least 1.4 nm (ref. 7 ), so even pores in atomically-thin membranes (such as those made of graphene, which are discussed in the Review by Stephanie Heerema and Cees Dekker 4 ) will be sensitive to the DNA bases that lie outside the pore on each side (Fig. 1a).…”
Section: Standfirstmentioning
confidence: 99%
“…It was shown that repetitive deposition cycles of ALD can be used to fabricate ultra‐thin solid membranes appropriate for low aspect ratio nanopores fabrication . ALD was also suggested to be able to coat all exposed surfaces including inside of the nanopore and thus effectively decrease nanopore diameter . Lee et al.…”
Section: Fabrication Of Solid‐state Nanoporesmentioning
confidence: 99%